2014
DOI: 10.4330/wjc.v6.i8.713
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training in hypertension: Role of microRNAs

Abstract: Hypertension is a complex disease that constitutes an important public health problem and demands many studies in order to understand the molecular mechanisms involving his pathophysiology. Therefore, an increasing number of studies have been conducted and new therapies are continually being discovered. In this context, exercise training has emerged as an important non-pharmacological therapy to treat hypertensive patients, minimizing the side effects of pharmacological therapies and frequently contributing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 125 publications
0
36
0
2
Order By: Relevance
“…miRNAs emerged as important regulators of gene expression and are implicated in most, if not all, cellular processes and several diseases [13,14,15,16,17,18,19,20,23,25,29]. miRNAs are able to target many genes with the possibility to modulate multiple pathways related to vascular remodeling and either can promote or inhibit structural changes of the vessel [17,18,19,20,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs emerged as important regulators of gene expression and are implicated in most, if not all, cellular processes and several diseases [13,14,15,16,17,18,19,20,23,25,29]. miRNAs are able to target many genes with the possibility to modulate multiple pathways related to vascular remodeling and either can promote or inhibit structural changes of the vessel [17,18,19,20,30].…”
Section: Discussionmentioning
confidence: 99%
“…Fish et al [31] showed the loss of vascular integrity and hemorrhage during embryonic development by knockdown of miRNA-126. miRNA-126 targets sprouty-related protein 1 (SPRED1) and phosphoinositol-3 kinase regulatory subunit 2 (PI3KR2), which negatively regulates VEGF signaling via VEGF receptor (VEGFR) 2, mitogen-activated protein kinase, and phosphatidylinositol 3-kinase (PI3K) pathways involved in angiogenesis [10,18,19,23,29,31]. …”
Section: Discussionmentioning
confidence: 99%
“…The miRNAs can associate with the 3’-untranslated regions of messenger RNAs (mRNAs) with imperfect base-pairing and negatively impact gene expression by mRNA degradation or inhibition of translation [85]. Several miRNAs have been implicated in hypertension-associated cardiac remodeling, and exercise training has been associated with reversal or prevention of the pathological cascade mediated by these miRNAs.…”
Section: Physical Activity and Cardiac Remodeling In The Hypertensivementioning
confidence: 99%
“…Several miRNAs have been implicated in hypertension-associated cardiac remodeling, and exercise training has been associated with reversal or prevention of the pathological cascade mediated by these miRNAs. Additional studies are needed to further understand these pathways and identify potential therapeutic targets [18,8587]. …”
Section: Physical Activity and Cardiac Remodeling In The Hypertensivementioning
confidence: 99%
“…miRNAs have been implicated in most diseases, either preserving physiological cell function or promoting pathological signaling and dysfunction. In cardiovascular diseases, major miRNAs have been thoroughly cataloged and analyzed; exciting miRNA targets have been found in atherosclerosis (70,90), heart failure (63), diabetes (88), and hypertension (91).…”
Section: Kruppel-like Factorsmentioning
confidence: 99%